The effectiveness of AR e-module of flower structure material on biology students’ science literacy - S. Sulisetijono; S. Sunarmi; Azizah Nur Rochmah (University of Muhammadiyah Malang, 2023)
The electronic-module (e-module) is one of the teaching materials needed so that the learning process can take place optimally. E-module owned by UM biology students generally do not use the latest technology. Augmented Reality (AR) is a form of technology where there is a process of integrating the virtual world with the real world. Not a few students experience difficulties in understanding the flower structure material. Student scientific literacy is still far from what is expected. The research conducted is Research and Development with the Lee and Owens Development Model. Data collection was carried out during October-December 2022. The technique of analyzing quantitative descriptive data. The subjects in this study were 37 biology students class of 2021 without any differences in gender, age and study program. The results of the effectiveness of the AR electronic-module based on n-gain calculations obtained a score of 0.7 where on that score the AR e-module was categorized as quite effective in increasing scientific literacy. It is hoped that in the future there will be teaching materials and media that can improve some of the competencies needed by the latest generation.